2016
DOI: 10.3109/07435800.2016.1155598
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the clinical usefulness of neck circumference and waist circumference in individuals with severe obesity

Abstract: In individuals with severe obesity, NC performs better than WC in the assessment of metabolic health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 23 publications
3
40
2
2
Order By: Relevance
“…This notion is supported by a previous study in which the combination SAD and WC showed the most accurate prediction of abdominal fat distribution as assessed by MRI [39]. Of note, other anthropometric measures like the neck circumference, not reflecting abdominal obesity, might further improve the prediction of metabolic alterations as has recently been shown in obese women and men [40]. SAD on the other hand has previously been shown to predict the risk of cancer incidence in a non-obese population [41] and also in subjects with severe obesity [42].…”
Section: Discussionsupporting
confidence: 72%
“…This notion is supported by a previous study in which the combination SAD and WC showed the most accurate prediction of abdominal fat distribution as assessed by MRI [39]. Of note, other anthropometric measures like the neck circumference, not reflecting abdominal obesity, might further improve the prediction of metabolic alterations as has recently been shown in obese women and men [40]. SAD on the other hand has previously been shown to predict the risk of cancer incidence in a non-obese population [41] and also in subjects with severe obesity [42].…”
Section: Discussionsupporting
confidence: 72%
“…Several researchers have reported similar associations of NC with BMI, WC, HC and WHR (Fink et al 2006;BenNoun and Laor 2006;Onat et al 2009;Hingorjo et al 2012;Adamu et al 2013;Aswathappa et al 2013Aswathappa et al , 2014Wang et al 2015;Özkaya and Tunçkale 2016). Furthermore, studies reported that NC has a potential role to surpassing excess adiposity marker over the conventional anthropometric measures (e.g., BMI, WC and WHR) in metabolic disorders (Onat et al 2009;Yang et al 2010;Adamu et al 2013;Aswathappa et al 2013;Wang et al 2015;Assyov et al 2016). The BMI has also shown a reasonably good correlation with the other conventional anthropometric variables of excess adiposity in adults (Dudeja et al 2001;Das and Bose 2006;Sarkar et al 2009;Hingorjo et al 2012;Aswathappa et al 2013).…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, it was opined that BMI can be used to determine and monitor changes in the prevalence of overweight/obesity (Dudeja et al 2001;Das and Bose 2006;Onat et al 2009;Mondal and Sen 2014;Rengma et al 2015). Recent studies have reported that NC has a potential role to play as an excess adiposity marker over the conventional anthropo-metric variables in metabolic disorders in adults (Onat et al 2009;Yang et al 2010;Aswathappa et al 2013;Adamu et al 2013;Wang et al 2015;Assyov et al 2016). The present study also showed a high prevalence of overall and regional adiposity using the conventional anthropometric variables (such as BMI, WC, WHR and WC/height) among adults (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1,7,15,21,(25)(26) Th is study showed that NTR is not the most appropriate measure to estimate MS in a popula- tion of Brazilian university students. However, NC and TC have been shown to be useful in predicting metabolic and cardiovascular dysfunctions related to the progression of diseases such as diabetes, atherosclerotic disease, systemic arterial hypertension, or others involving the accumulation of visceral and subcutaneous adiposity, infl uencing the development of components for MS. (27)(28)(29)(30) In the analysis of the correlation between NTR and MS componentes, it was observed that the establishment of this anthropometric index has a positive impact with almost all, being an excellent indicator of risk through these biomarkers. Changes in biomarkers that signal MS, indicated by the NTR, are directly linked to the genesis of overweight/obesity, which in turn are the main determinants of dyslipidaemia, diabetes and hypertension.…”
Section: Discussionmentioning
confidence: 99%